Optimal large‐scale CD34+ enrichment from a leukapheresis collection using the clinimacs prodigy platform - Pello, Oscar M. (Clin Case Rep, 2020)
Optimization of Hematology Patient's treatment: It is possible to obtain a 100% CD34+ recovery after CD34+ selection using the CliniMACS Prodigy.